Tolerability of amodiaquine and sulphadoxine-pyrimethamine, alone or in combination for the treatment of uncomplicated Plasmodium falciparum malaria in Rwandan adults. - Fanello, C; Karema, C; van Doren, W; Rwagacondo, C; D'Alessandro, U (2006)
OBJECTIVE: To assess the tolerability and efficacy of amodiaquine (AQ)+sulphadoxine-pyrimethamine (SP), the first-line malaria treatment in Rwanda. METHOD: Randomized, double-blind trial in 2003 in Kigali town. A total of 351 adult patients with uncomplicated Plasmodium falciparum malaria were randomly allocated to one of the following treatments: AQ+SP, AQ or SP. We followed patients until day 14 after treatment and recorded adverse events (AEs) and clinical and parasitological outcomes. RESULTS: One hundred and eighteen patients reported at least one AE: 40% in the AQ, 39% in the AQ+SP and 21% in the SP groups. The AE was classified as possibly related to the antimalarial treatment for 86 patients. The Risk Ratio for at least one AE after treatment was significantly and about fourfold higher in patients receiving AQ or AQ+SP than in patients receiving SP. Pruritus and fatigue were significantly more frequent in patients treated with AQ or AQ+SP than in those receiving SP. Severe AEs, such as fatigue, nausea, dizziness and vomiting, were observed in four patients treated with AQ, in 10 treated with AQ+SP and in one patient treated with SP. CONCLUSION: Amodiaquine+SP is not well tolerated and a substantial proportion of patients experienced pruritus and fatigue, thus decreasing their compliance and compromising the first line treatment implementation at national level. This renders AQ-containing regimens sub-optimal; better-tolerated treatments should be identified.